An Investigation of Genetic and Environmental Influences Across the Distribution of Self-Control - Schwartz, Joseph A. (Criminal justice and behavior, 2017)
Previous research illustrating a robust, negative association between self-control and various forms of delinquent and criminal behavior has resulted in a more concentrated focus on the etiological development of self-control. The current study aims to contribute to this literature using a sample of twin and sibling pairs from the National Longitudinal Study of Adolescent to Adult Health (Add Health) to examine genetic and shared environmental influences across levels of self-control. The results of modified DeFries-Fulker (DF) equations revealed that genetic and shared environmental influences were distributed in a nonlinear pattern across levels of self-control. Subsequent biometric quantile regression models revealed that genetic influences on self-control were maximized in the 50th and 60th percentiles, and minimized in the tails of the distribution. Shared environmental influences were nonsignificant at all examined quantiles of self-control with only one exception. The theoretical importance of utilizing genetically informed modeling strategies is discussed in more detail.